Directly Printable Frequency Signatured Chipless RFID Tag for IoT Applications - Anam H; Habib A; Jafri SI; Amin Y; Tenhunen H (SPOLECNOST PRO RADIOELEKTRONICKE INZENYRSTVI, 2022)
This paper proposes a low-cost, compact, flexible passive chipless RFID tag that has been designed and analyzed. The tag is a bowtie-shaped resonator based structure with 36 slots; where each patch is loaded with 18 slots. The tag is set in a way that each slot in a patch corresponds to a metal gap in the other patch. Hence there is no mutual interference, and high data capacity of 36 bits is achieved in such compact size. Each slot corresponds to a resonance frequency in the RCS curve, and each resonance corresponds to a bit. The tag has been realized for Taconic TLX-0, PET, and Kapton (R) HN (DuPont (TM)) substrates with copper, aluminum, and silver nanoparticlebased ink (Cabot CCI-300) as conducting materials. The tag exhibits flexibility and well optimized while remaining in a compact size. The proposed tag yields 36 bits in a tag dimension of 24.5. 25.5 mm(2). These 36 bits can tag 2(36) number of objects/items. The ultimate high capacity, compact size, flexible passive chipless RFID tag can be arrayed in various industrial and IoT-based applications.